2017
DOI: 10.1002/jcu.22566
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial fetus‐in‐fetu with numerous fully developed organs

Abstract: Fetus in fetu (FIF) is an extremely rare anomaly featuring a monozygotic, diamniotic, parasitic twin, enclosed within its host twin. It is characterized by the presence of vertebrae and well-developed organs in a fetiform mass. Only 18 cases of intracranial FIF have been published. Of them, only five cases were prenatally detected. This study prenatally demonstrated triplet FIFs at 31 weeks within amniotic-like sac in the fetal skull, consisting of multiple well-defined organs. The FIF attached to the host twi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 23 publications
0
8
1
4
Order By: Relevance
“…Contrary to this report, Traisrisilp et al 16 found a female fetus with intracranial fetal organ structure associated with hydrocephalus. In that case, the pathological examination confirmed the diagnosis of FIF.…”
Section: /6contrasting
confidence: 77%
“…Contrary to this report, Traisrisilp et al 16 found a female fetus with intracranial fetal organ structure associated with hydrocephalus. In that case, the pathological examination confirmed the diagnosis of FIF.…”
Section: /6contrasting
confidence: 77%
“…FIF is a condition, commonly occurs in retroperitoneal space (80%) 2. Others rare sites like sacrococcygeal region, intracranial, thorax, pelvis, scrotum, back and oral cavity have also been described in the literature 3–5. There are two theories for the development of FIF.…”
Section: Discussionmentioning
confidence: 99%
“…FIF often show characteristic human development with presence of organs, tissues, and/or hair. They are mostly found in the retroperitoneum, but can also be found in the abdominal cavity, cranial cavity, sacrum, mediastinum, scrotum, oral cavity, kidneys, and even as cryptorchidism (1,(9)(10)(11). Clinically, it typically manifests as abdominal distension and a painless mass in the abdomen.…”
Section: Introductionmentioning
confidence: 99%